Tetrathienothiophene Porphyrin as a Metal-Free Sensitizer for Room-Temperature Triplet–Triplet Annihilation Upconversion - Vasilev, Aleksey; Kostadinov, Anton; Kandinska, Meglena; Landfester, Katharina; Baluschev, Stanislav (Frontiers in Chemistry, 2022)
Optically excited triplet states of organic molecules serve as energy pool for the subsequent processes, either photon energy downhill such as room temperature phosphorescence or photon energy uphill process – the triplet-triplet annihilation upconversion (TTA-UC). Manifestation of a high intersystem crossing coefficient is an unavoidable requirement for triplet state formation, following absorption of a single photon. This requirement is even more inevitable, if the excitation light is non-coherent, with moderate intensity and extremely low spectral power density, comparable with the light parameters of 1 Sun (1.5 AM). Coordination of a heavy atom increases substantially the probability for intersystem crossing. Nevertheless, having in mind the global shortage in precious- and rare-earths- metals, identification of metal-free organic moieties able to form triplet states becomes prerequisite for environmental friendly optoelectronic technologies. This motivates us to synthesize a metal-free thienothiophene containing porphyrin, based on a condensation reaction between thienothiophene-2-carbaldehyde and pyrrole in an acidic medium by modified synthetic protocol. The upconversion couple tetrathienothiophene porphyrin / rubrene when excited at 658 nm demonstrates bright, delayed fluorescence with emission maximum at 555 nm. This verify our hypothesis, that the ISC-coefficient in thienothiophene porphyrin is enough efficient in order to create even at room temperature and low-intensity optical excitation densely populated organic triplet ensemble, able for photon energy uphill processes, which makes this type of metal-free sensitizers even more important for optoelectronic applications